TINJAUAN HUKUM ISLAM TENTANG PENGGUNAAN UANG ELEKTRONIK DAN RELEVANSINYA TERHADAP LAHIRNYA FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA - Alhusni, Alhusni (Nurani, 2019)
Electronic money as a policy amid advances in banking technology and the demands of the needs of the community for alternative payment that is fast and safe. But behind these advantages, still as Muslims, it is necessary to know and ensure the views of Islamic law regarding the use of electronic money for payment transactions, transfers, cash withdrawals and refunds. By using the library research method, this paper discusses several issues including: First, how Islamic law views the use of electronic money. Second, the relevance of Islamic law to the fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI). Based on the findings and analysis conducted that the use of electronic money is permissible in Islamic law. Because transactions using electronic money are the same as transactions that previously developed in the banking system, such as credit cards. Even though the buyer and seller do not meet in person. However, in transactions using electronic money a joint "agreement" was found. Indirectly between the two agreed because there is no change between the price offered and the paid value, the buyer who wants to buy also knows the price in full. Various types of special payments such as e-toll, e-ticketing, e-parking, e-pospay and so on. Specifically in religious (Islamic) authorization in Indonesia, financial transactions enter the authority of the National Sharia Council-Indonesian Ulema Council (DSN-MUI). So the DSN-MUI fatwa is closely related to the contract process. Based on this, the use of e-money, at least fulfills four elements of contract in Islam, namely, contract of sale, contract of wadiah (safekeeping of goods / property), contract of ijarah (transfer of usufructuring rights) and contract of wakalah (surrender authority). So from this it can be concluded that the fatwa on electronic money issued by the DSN-MUI is very relevant. Keywords: electronic money, Islamic law, DSN-MUI fatwa